Empathy Fatigue: Healing the Mind, Body, and Spirit of Professional Counselors - STebnicki Mark A (Springer, 2008)
Many mental health practitioners present symptoms that are consistent with their clients' anxiety and stress-related disorders. It comes as no surprise, then, that "counselor impairment" - the stress that comes from treating survivors of traumatic events - is now officially recognized by the American Counseling Associations' Task Force on Counselor Wellness.